2012
DOI: 10.1007/s10620-012-2271-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Types of Precut Technique to Achieve Common Bile Duct Cannulation: A Retrospective Analysis of 274 Cases

Abstract: The three types of precut sphincterotomy have no different overall CBD cannulation rates; SPF reduces post-ERCP pancreatitis risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 20 publications
8
47
0
9
Order By: Relevance
“…Lower PEP rate was observed in early precut group (5.4% vs 12.1%) . If the patient with common bile duct dilation down to the papilla, some studies suggested fistulotomy is the preferred precut technique …”
Section: Risk Factorsmentioning
confidence: 99%
“…Lower PEP rate was observed in early precut group (5.4% vs 12.1%) . If the patient with common bile duct dilation down to the papilla, some studies suggested fistulotomy is the preferred precut technique …”
Section: Risk Factorsmentioning
confidence: 99%
“…81 In a retrospective analysis of patients in which > 80% had pancreatography but only 10% underwent pancreatic stenting, risk of PEP was low (3%) after NKF compared to either NKS or TPP that was associated with a high risk for PEP (> 20%). 82 Jin et al 83 recently reported no cases of PEP when NKF was utilized as a primary access technique before any standard cannulation methods in patients with bile duct stones. However, the risk of NKF is likely higher in patients with small diameter bile ducts.…”
Section: Procedures Techniquesmentioning
confidence: 99%
“…If feasible, a prophylactic pancreatic stent should be placed as there is a significant risk of PEP. There are also potential long-term consequences of a pancreatic sphincterotomy, such as pancreatic orifice stenosis [8]. • Intramural incision technique: This technique utilizes the false tract that can be created by the guide wire during biliary cannulation attempts.…”
Section: Less Common Precut Techniquesmentioning
confidence: 99%